Cover Image, Volume 43, Issue 7. (23rd May 2019) - Pan, Zhefei; Huang, Bin; An, Liang
Abstract : The cover image is based on the Special Issue ‐ Research Article Performance of a hybrid direct ethylene glycol fuel cell by Zhefei Pan et al., https://doi.org/10.1002/er.4176 .